2000
DOI: 10.1164/ajrccm.162.4.9912033
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Allergic Rhinitis and Asthma

Abstract: Quality of life has been found to be impaired both in patients with asthma and in patients with allergic rhinitis, but the relative burden of these diseases has not been investigated. We analyzed answers to the SF-36 questionnaire from 850 subjects recruited in two French centers participating in the European Community Respiratory Health Survey, a population-based study of young adults. Both asthma and allergic rhinitis were associated with an impairment in quality of life. However, 78% of asthmatics also had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
78
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(95 citation statements)
references
References 34 publications
9
78
1
4
Order By: Relevance
“…In agreement with Leynaert et al (2000), (1) we found that patient with allergic rhinitis suffer from signicantly lower quality of life if compared with control. Further impairment was noticed in asthmatic patients with or without allergic rhinitis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with Leynaert et al (2000), (1) we found that patient with allergic rhinitis suffer from signicantly lower quality of life if compared with control. Further impairment was noticed in asthmatic patients with or without allergic rhinitis.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, we found that reduced PCS is significantly correlated with the severity of asthma as assessed by FEV 1 level as previously stated. (1,23,24) In concordance with Leynaert and co workers, (1) individual analysis revealed that older age and longer duration of symptoms considered as risk factors for reduced HRQOL, particularly in patients with both asthma and allergic Rhinitis, as they were the oldest group with the longest duration of symptoms. Moreover, Patients with a BMI less than 25 kg/m 2 were shown to have better SF-36 scores in all domains that also add another risk factor for reduction in HRQOL in asthmatics as they had higher BMI if compared with other groups.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Leynaert et al 25 comprovaram que a relação entre a gravidade da RA e piora da qualidade de vida é mais evidente em mulheres, conforme os dados mostrados na tabela 3.…”
Section: Discussionunclassified
“…Por otra parte, el empleo en este estudio del SF-36 permitió comparar el resultado relativo al asma y la rinitis alérgica con otras enfermedades (40). Un beneficio adicional fue conocer la diferencia mínima clínicamente significativa, lo que permitió confirmar que los cambios en los valores promedio entre los dominios del SF-36 superiores a nueve puntos eran clínicamente importantes, justificando, igualmente, subsecuentes modificaciones en el tratamiento de los pacientes (13).…”
Section: Rinitisunclassified